The Relationship Between Eating Junk Food and a Sedentary Lifestyle with Obesity in Elementary School Children - Ummah, Faridatul; Indanah, Indanah; Purnomo, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: Obesity is a long-term condition caused by the accumulation of fat in the body due to an imbalance between energy intake and expenditure. This study aims to investigate the relationship between junk food consumption and a sedentary lifestyle, as well as the incidence of obesity, among elementary school children, particularly at SD 1 Megawon, Kudus Regency. This study also aims to understand the types of fast food consumed and the duration of sedentary behavior in children. Research Method: The research design employed was quantitative, utilizing a correlational analytical approach and a case-control design. The study was conducted at SD 1 Megawon in March 2025. The sample consisted of 60 respondents, namely 30 children with obesity and 30 children without obesity, selected using purposive sampling. Data were collected through the Food Frequency Questionnaire (FFQ) to assess junk food consumption habits and the Adolescent Sedentary Activity Questionnaire (ASAQ) to measure sedentary activity. Data analysis was performed using bivariate analysis with the chi-square test. Results and Discussion: The results indicate a significant relationship between the frequency of junk food consumption and sedentary activity levels, as well as obesity, in elementary school children. The p-values for both variables indicate statistical significance (p < 0.05). Implications: These findings provide a crucial foundation for schools and parents to implement healthy eating patterns and encourage physical activity, thereby preventing childhood obesity from an early age.